Disrupsi Pandemi dan Strategi Pemulihan Industri Kreatif - Rudi Santoso (JMK (Jurnal Manajemen dan Kewirausahaan), 2022)
This study offers a theoretical follow-up discussion on the implementation of public finance strategies and policies used to help the creative industry from the disruption of the COVID-19 pandemic. This article also presents various policies that have been taken by the government with a fiscal approach. The policies used by the government have also been replicated by countries in the Southeast Asian region that are members of ASEAN. This research focuses on the integration of research on the pattern of the creative industry economy with the contemporary paradigmatic discourse of the creative industry. This study proves that the fiscal policy strategy used by the government is able to reduce the slump in the national economy. This study found that there was uniformity in the pattern of economic recovery policies in the Southeast Asia region to respond to COVID-19. This uniform pattern is related to stimulus policies in 6 (six) important sectors, one of which is the creative industry. This research also finds that the pattern used in the policy is to focus on incentives for creative industry players, creative industry roadmap, creative economy training, legal protection of creative economy products, and investors for development.